Aspectos bionômicos de Geometridae (Lepidoptera) Erythroxylum microphyllum (Erythroxylaceae) na região de São Carlos, SP - Marconato, Gláucia (2001)
This work was carried out in a Cerrado area near to riparian forest. We studied the Geometridae associated to Erythroxylum microphyllum. The samples were collected at each two weeks, during a year. Its was used the method of entomological umbrella. The larvae was grown in the laboratory, using the host plant as food. It occured 22 species of Geometridae arranged in 15 genus, 11 genus of Hymenoptera Parasitca and two Diptera Tachindae. The most common species that occured was Cyclomia mopsaria, whose relative abundance was 83%. Other Geometridae recorded were: Glena unipennaria, G. bipennaria, G. demissaria, G. brachia, Physocleora junctilinea, P. cariaria, Physocleora sp., Iridopsis fulvitincta, I. nigraria, Hymenomima amberia, Macaria regulata, Ischnopteris sp., Prochoerodes onustaria, Prochoerodes sp., Thyrinteina arnobia, Nematocampa sp., Melanolophia sp., Isochromodes, Semaeopus lunifera and Semaeopus vizaria. The Hymenoptera parasitoids were: Microcharops peronata, Charops sp., Metopius sp., Hyposoter sp., Mesochorus sp., Aleiodes sp., Distatrix sp., Meteorus sp., Protapanteles sp., Rasivalva sp., e Euplectrus sp. The Diptera Tachinidae were: Winthemia sp., and a Blondeliini species. The period of higher occurrence of larvae was between the end of rainy season and the begining of the dry season. At this same period, was recorded the lowest rate of parasitism.